Internal Control Effectiveness of Financial Management In Private Higher Education - Ernawati Ernawati; Imam Agus Faisol (JAFFA, 2020)
This research investigates internal control effectiveness in supporting financial management of higher education institutions. The object of this research is an Internal Supervisory Unit at a private higher education named "Kelabu College" on island X. This research uses qualitative method with interview, observation, and documentation techniques. The research results show that the role of internal supervisory unit in investigating and controlling financial of higher education institutions has not been fully implemented. The research results also show that the aspect of internal control such as monitoring activities and risk assessment has not been carried out properly. While, aspects of information and communication, control activities, and control environment have been well implemented.